Effects of Aquatic Exercise Training on Pain, Symptoms, Motor Performance, and Quality Of Life of Older Males with Knee Osteoarthritis - Soleyman Ansari; Alireza Elmieh; Zahra Hojjati (The Society of Aging and Physical Activity (SAPA), 2014)
Clinical experiences indicate that aquatic exercises may have advantages for osteoarthritis patients. The purpose of this study was to examine the effects of aquatic exercise training on the knee pain and its symptoms as well as on the motor performance associated with daily living activities (ADL), sport-recreational activities, and the quality of life in men over 50. 30 men over 50 years old who suffered from knee osteoarthritis were selected voluntarily and were randomly assigned to aquatic exercise therapy and control groups. The means and standard deviations of age, height and weight of participants in each group were 54.26 ± 3.08 and 57.6 ± 5.76 yr; 169 ± 4.99 and 168.13 ± 4.76 cm; and 76.33 ± 8.11 and 71.53 ± 8.09 kg, respectively. Aquatic exercise training was carried out 3 times per week for 6 weeks. Knee pain, symptoms, motor function in daily activities and sport- recreation and quality of life were measured before and after exercise training. Results showed that the knee pain, symptoms, motor function in daily and sports - recreational activities and quality of life after the exercise protocol significantly improved in the aquatic exercise group (P < 0.05); however, there was no significant change in control groups from pre to post-test (p> 0.05). The results showed that aquatic exercises, as a safe and effective exercise method, could be incorporated to improve the pain, motor functions and quality of life in over-50-year-old males with knee osteoarthritis.